Tetanus-induced rhythmic seizures mimicking the clinical and electroencephalographic presentation of status epilepticus. Issue 9 (9th September 2022) - Lequain, Hippolyte; Richard-Mornas, Aurelie; Argaud, Laurent; Dargent, Auguste
Abstract : We describe the case of a woman in her 60s admitted to the intensive care unit after a first generalised tonic-clonic seizure in the context of alcohol withdrawal. She was placed under invasive mechanical ventilation due to persistence of coma despite antiepileptic treatment. Despite continuous sedation with propofol, the frequency and intensity of seizure increased. Seizures were very similar to epileptic tonic-clonic seizures and were recorded with video and electroencephalogram (EEG). A diagnosis of tetanus was considered after a scalp wound was discovered. The patient's husband revealed that a trismus had appeared a few days before hospital admission after a head trauma. EEG showed a pattern of diffuse spikes, which disappeared after a cisatracurium bolus. The diagnosis of tetanus was later confirmed by cultures from wound samples. Therefore, severe tetanus can mimic both the clinical and EEG features of status epilepticus and could be added to the differential diagnosis of epilepsy.